2017
DOI: 10.1016/j.jconrel.2016.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Thermally triggered release of the bacteriophage endolysin CHAPK and the bacteriocin lysostaphin for the control of methicillin resistant Staphylococcus aureus (MRSA)

Abstract: Staphylococcus aureus infections of the skin and soft tissue pose a major concern to public health, largely owing to the steadily increasing prevalence of drug resistant isolates. As an alternative mode of treatment both bacteriophage endolysins and bacteriocins have been shown to possess antimicrobial efficacy against multiple species of bacteria including otherwise drug resistant strains. Despite this, the administration and exposure of such antimicrobials should be restricted until required in order to disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 42 publications
4
50
0
Order By: Relevance
“…While no bacterial lysis in the presence of the NPs occurred at 32°C (the temperature of healthy skin), numbers of S. aureus bacteria were reduced by Ͼ4 log units when the temperature was increased to 37°C, owing to the release of the active enzyme mix. CHAP K and lysostaphin were chosen for these experiments due to their demonstrated synergistic effect when used in combination (199).…”
Section: Nanotechnology As a New Strategy For Endolysin Deliverymentioning
confidence: 99%
“…While no bacterial lysis in the presence of the NPs occurred at 32°C (the temperature of healthy skin), numbers of S. aureus bacteria were reduced by Ͼ4 log units when the temperature was increased to 37°C, owing to the release of the active enzyme mix. CHAP K and lysostaphin were chosen for these experiments due to their demonstrated synergistic effect when used in combination (199).…”
Section: Nanotechnology As a New Strategy For Endolysin Deliverymentioning
confidence: 99%
“…In the study, the combination of nisin and EDTA showed a synergistic effect but the combination of nisin and bacteriophage did not. Hathaway et al (2017) designed a nanoparticle harboring a bacteriophage endolysin and a bacteriocin for controlling methicillin-resistant S. aureus (MRSA) on human skin that could release the included molecules by temperature control. The nanoparticles worked effectively at 37℃, the temperature associated with skin wounded by infection, and cell lysis was observed.…”
Section: Synergistic Inhibition Of S Aureus Growth By the Bacteriocimentioning
confidence: 99%
“…Additionally, recent advances in therapy using bacteriophage products, namely bacteriophage-encoded endolysins, which are utilised in end stages of phage infection, and care capable of enzymatically degrading the bacterial cell wall through digestion of the peptidoglycan polymeric material, resulting in cell death by osmolysis. 38 Endolysins have been use synergistically with antibiotics to give increased antibiotic activity against otherwise resistant Gram-negative strains. 53 Other factors potentially hindering phage efficacy include the inhibition of phage adhesion to their bacterial hosts owing to the accumulation of struvite and apatite crystalline precipitates, or the physiological state of the cells themselves, since log-phase cells are lysed more efficiently than those in a state of partial or full metabolic quiescence (such as those within a biofilm).…”
Section: Activation Of Catheter Coating: Effect On Catheter Blockagementioning
confidence: 99%
“…33,34 Recently, emphasis has been placed on developing methods of active, or triggered release of antimicrobial agents in response to external stimuli (e.g. pH, [35][36][37] temperature, 38,39 or biomarker signals 40 ), in order to achieve a 'burst response' of the active cargo. Triggered release formulations can be used to reduce the amount of drug necessary to cause the same therapeutic effect in patients, as well as ensuring that the cargo is released only in the physiological location required, thus reducing systemic dosage and its associated complications.…”
Section: Introductionmentioning
confidence: 99%